The laws of robots : crimes, contracts, and torts - Pagallo, Ugo (Law, Governance and Technology Series, 2013)
This book explores how the design, construction, and use of robotics technology may affect today's legal systems and, more particularly, matters of responsibility and agency in criminal law, contractual obligations, and torts. By distinguishing between the behaviour of robots as tools of human interaction, and robots as proper agents in the legal arena, jurists will have to address a new generation of "hard cases." General disagreement may concern immunity in criminal law (e.g., the employment of robot soldiers in battle), personal accountability for certain robots in contracts (e.g., robo-traders), much as clauses of strict liability and negligence-based responsibility in extra-contractual obligations (e.g., service robots in tort law). Since robots are here to stay, the aim of the law should be to wisely govern our mutual relationships.